(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the medication adherence and related factors in patients with hepatitis B virus infection at Thanh Son regional Medical Center, Phu Tho province in 2025. Subjects and methods: A cross-sectional study. The research subject is hepatitis B patients who had been using antiviral medication for 3 months or more at Thanh Son regional Medical Center. Results: In the study of 162 subjects, most patients were low medication adherence, about 59.3%. Analysis showed that the medication adherence was related to factors such as age (p < 0.001), occupation (p = 0.024), and income (p < 0.001). Futhernore, having family members with hepatitis B was associated with a 2.465-fold increase in medication adherence (p = 0.04), while a treatment duration of ≥ 6 years was associated with a 12.491-fold increase (p < 0.001). Conclusion: The level of medication adherence in hepatitis B patients was low. Demographics factors, as well as family history and duration of treatment, significantly influence the medication adherence. This suggest the need for appropriate interventions to enhanve medication adherence outcomes in this patient group.